Oxyhemodynamic repercussions of lateralization of patients up to 72 h after acute coronary syndrome: clinical trial (Research, Society and Development, 2020)
Objective: to analyze the impact of dorsal, left and right lateral positions of patients with acute coronary syndrome on oxyhemodynamic variables. Method: Randomized, uncontrolled, single-blinded clinical trial, performed at the Coronary Unit of a private hospital in Niterói, Brazil. The impact of positioning in the supine position, left and right sides on the following variables was analyzed: heart rate, stroke volume, heart index, systolic blood pressure, diastolic blood pressure, mean arterial pressure, cardiac work index, maximum ventricular contraction and O2 consumption, measured using an impedance cardiography device. The randomization of the initial lateral decubitus position was performed with the aid of an electronic spreadsheet. Convenience sample made up of 16 consecutively recruited volunteers. For the comparison of means, analysis of variance (ANOVA) and t-Student test for paired samples were performed, with a pre-established significance level of 5%. Results: Mostly male sample, with an average age of 67 ± 11 years, non-alcoholic and non-smoker. Systolic blood pressure showed a significant decrease in the right lateral and dorsal decubitus (p < 0.01), not reflected in changes in mean arterial pressure. The other variables showed noticeable oscillations in the left lateral decubitus, without statistical significance. Conclusion: The change in position of patients with coronary syndrome, hemodynamically stable, is safe and does not have a deleterious impact on the oxyhemodynamic variables. One must consider the clinical repercussions that occurred in the left lateral decubitus, to support decision-making in clinical practice.